Eksistensi Lembaga Adat: Studi Kasus Lembaga Adat Melayu Jambi Tanah Pilih Pasko Batuah Kota Jambi dan Tinjauan Kritis terhadap Perda No. 5 Tahun 2007 - Armida, Armida (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2010)
In consciousness or not, globalization and modernizationhas eroded the local culture. This article discusses the existenceof Lembaga Adat Melayu Jambi (Jambi Malay CustomaryInstitution) in preserving and maintaining the local culture. InJambi, the task was reinforced by Peraturan Daerah (RegionalRegulation) No. 5 of 2007. Therefore, this article also focuses onits effectiveness. As a result, traditional institutions have notimplemented their tasks and functions properly. Actual conditionsrecorded that this institution have no professional andindependent organization systems. They have very limitedfunction, merely ceremonial. This is mainly due to policyimplementation that has not followed the instructions of localregulations and an having adequate budget.